Effects of atazanavir, darunavir, and raltegravir on fat and muscle among persons living with HIV. Issue 4 (31st August 2020) - Adrian, Stefan; Miao, Hongyu; Feng, Han; Scherzinger, Ann; Nardini, Giulia; Beghetto, Barbara; Roncaglia, Enrica; Ligabue, Guido; Milic, Jovana; Guaraldi, Giovanni; Lake, Jordan E.; Erlandson, Kristine M.
Abstract : Background: Antiretroviral therapy (ART) is associated with gain in quantity of fat and muscle, but the impact on quality is less understood. The objective of this study was to compare fat and muscle density among people with HIV (PWH) on stable raltegravir (RAL), atazanavir with ritonavir (ATV/r), or darunavir with ritonavir (DRV/r), and explore implications on muscle function. Methods: Participants from the Modena HIV Metabolic Clinic taking RAL, ATV/r, or DRV/r with at least 1 computed tomography (CT) scan were included. CT scans were reanalyzed for area and density of truncal fat and musculature. Multivariate models explored the effect of ART on fat and muscle density. Results: One hundred six participants were receiving ATV/r, 48 DRV/r, and 141 RAL. In multivariate models (reference ATV/r), only DRV/r was associated with greater subcutaneous (SAT) and visceral adipose tissue (VAT) area, lower lateralis muscle density (more fat), and greater lateralis intermuscular fat area. Compared to ATV/r, RAL was independently associated with less psoas intermuscular fat area. Among all, greater paraspinal muscle density correlated with better physical function. No associations between ART group and physical function were seen among men; DRV/r was associated with stronger grip strength among women. Conclusion: DRV/r was associated with greater fat area and lower density of both fat and muscle, and RAL with less intermuscular psoas fat. Higher density psoas and paraspinal musculature were associated with better physical function, suggesting potential clinical relevance of these findings.